Controlling the Length of Cooperative Supramolecular Polymers with Chain Cappers. Issue 44 (17th June 2020) - ter Huurne, Gijs M.; Chidchob, Pongphak; Long, Augustin; Martinez, Alexandre; Palmans, Anja R. A.; Vantomme, Ghislaine
Abstract: The design and the characterization of supramolecular additives to control the chain length of benzene‐1, 3, 5‐tricarboxamide (BTA) cooperative supramolecular polymers under thermodynamic equilibrium is unraveled. These additives act as chain cappers of supramolecular polymers and feature one face as reactive as the BTA discotic to interact strongly with the polymer end, whereas the other face is nonreactive and therefore impedes further polymerization. Such a design requires fine tuning of the conformational preorganization of the amides and the steric hindrance of the motif. The chain cappers studied are monotopic derivatives of BTA, modified by partial N ‐methylation of the amides or by positioning of a bulky cyclotriveratrylene cage on one face of the BTA unit. This study not only clarifies the interplay between structural variations and supramolecular interactions, but it also highlights the necessity to combine orthogonal characterization methods, spectroscopy and light scattering, to elucidate the structures and compositions of supramolecular systems. Abstract : Chain cappers are additives that reduce the length of supramolecular polymers. Designing an ideal chain capper for cooperative supramolecular polymers of discotics requires a fine control of the reactivity of the noncovalent bonds. Both conformational organization of the reactive units and steric hindrance of the motifs are important elements.